واقع التنمر الوظيفي في الوظيفة العمومية - بغو,هواري (University of Eloued جامعة الوادي, 2024)
ملخص: هدفت الدراسة الحالية الى الكشف عن مستوى التنمر الوظيفي بأبعاده التنمر النفسي، التنمر اللفظي والتنمر الإجتماعي على موظفي ولاية أم البواقي، استخدم الباحث المنهج الوصفي، اعتمد على الاستبيان كأداة لجمع البيانات وقدرت عينة الدراسة بــــ 36 موظفا. توصلت النتائج الى أن نسبة 72,3% من عينة الدراسة لا يتعرضون إلى التنمر الوظيفي بأبعاده الثلاثة وما نسبته 23,2% مستوى التنمر الوظيفي عليهم متوسط ، أما النسبة الباقية المقدرة بـ 4,5% تتعرض إلى مستويات مرتفعة من التنمر الوظيفي. توصلت النتائج أيضا أنه لا توجد فروق ذات دلالة إحصائية في مستوى التنمر الوظيفي لدى عينة الدراسة تعزى لمتغير الجنس، في حين توجد فروق تعزى لمتغير الفئة السوسيومهنية. Abstract: The current study aimed to reveal the level of occupational bullying in its dimensions: psychological bullying, verbal bullying, and social bullying against employees of the state of Oum El Bouaghi. The researcher used the descriptive approach in both exploration and comparison methods, relied on the questionnaire as a tool for collecting data, and the study sample was estimated at 43 employees. The results revealed that 72.3% of the study sample are not exposed to occupational bullying in its three dimensions, 23.2% have an average level of occupational bullying, and the remaining percentage, estimated at 4.5%, are exposed to high levels of occupational bullying. The results also found that there are no statistically significant differences in the level of occupational bullying among the study sample due to the gender variable, while there are differences due to the socio-professional category variable.
دراسة ميدانية بمقر ولاية أم البواقي
Keywords: تنمر وظيفي; تنمر نفسي; تنمر لفظي; تنمر إجتماعي; Occupational bullying; psychological bullying; verbal bullying; social bullying